Surgical Treatment Assessment of Cervical Laminoplasty Using Quantitative Performance Evaluation in Elderly Patients: A Prospective Comparative Study in 505 Patients With Cervical Spondylotic Myelopathy. Issue 9 (May 2016) - Machino, Masaaki; Yukawa, Yasutsugu; Imagama, Shiro; Ito, Keigo; Katayama, Yoshito; Matsumoto, Tomohiro; Inoue, Taro; Ouchida, Jun; Tomita, Keisuke; Ishiguro, Naoki; Kato, Fumihiko
Abstract : Study Design: A prospective cohort study. Objective: The purpose of this study was to compare surgical outcomes between non-elderly and elderly patients with cervical spondylotic myelopathy (CSM) who underwent laminoplasty. Summary of Background Data: Since age at the time of surgery influences the surgical outcome, we designed a large-scale cohort study to examine the surgical outcome for CSM from a single operative procedure used exclusively in elderly patients. Methods: A total of 505 consecutive patients with CSM (311 men; 194 women) were prospectively enrolled. The mean age was 66.6 years (range, 41–91), and the average postoperative follow-up period was 26.5 ± 12.5 months. Patients were divided into three groups according to age: non-elderly (<65 yr, n = 201), young–old (65–74 yr, n = 186), and old–old (≥75 yr, n = 118). Pre- and postoperative neurological status was evaluated using the Japanese Orthopaedic Association scoring system for cervical myelopathy (JOA score) and quantifiable tests—the 10-s grip and release test (10-s G&R test) and the 10-s step test. Results: Mean achieved JOA scores in non-elderly, young–old, and old–old groups were 3.1, 3.2, and 3.0, respectively, with no significant difference among three groups ( P = 0.5735). Mean preoperative 10-s G&R test results were 17.3, 14.4, and 13.0, respectively, indicating a significant decrease with increasing age, whereas postoperative results significantly improved in all groups (21.0, 17.9, and 16.3, respectively). Similarly, the 10-s step test significantly decreased with age, with preoperative scores of 14.3, 11.5, and 8.6, respectively, whereas postoperative scores improved to 17.3, 14.9, and 12.5, respectively. The three groups showed no significant difference in the rate of postoperative complications. Conclusion: Elderly patients adequately recovered from laminoplasty in terms of achieved JOA score, the 10-s G&R test, and the 10-s step test. Therefore, laminoplasty for CSM is beneficial in elderly patients. Level of Evidence: 2